2019
DOI: 10.9734/asrj/2019/v2i130041
|View full text |Cite
|
Sign up to set email alerts
|

Role of Mineral and Bio-fertilizers on Some Soil Properties and Rice Productivity under Reclaimed Saline Soils

Abstract: A field experiment (randomized complete blocks with three replicates) was conducted during two successive summer seasons of 2016 and 2017 at Sahl El-Houssinia Agriculture Research Station in El-Shakia Governorate, Egypt. Its lies between 32˚00/00 to 32˚15/00/ N latitude and 30˚50 / 00// to 31˚15 00// E longitude. The combined effect of bio-fertilizers inoculated with Rhizobium radiobacter sp strain (salt tolerant PGPR); Bacillus megatherium (dissolving phosphate) and Bacillus circulans (enhancing potassium ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
0
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 9 publications
3
0
0
Order By: Relevance
“…P. concerning soil pH, the studied soil fell into the normal category, while it falls into the high category of salinity expressed as dSm -1 .based on FAO (1979) the studied soil is considered non-calcareous soil due where the CaCO 3 percentage is less than 15%. These findings agree with many studies carried out in the same study area (AbdElghany et al, 2019, Ali et al, 2014, Ibrahim et al, 2015, Mohaseb et al, 2019, Nasef et al, 2009, and Shaban et al, 2010. Table 1 shows that all soil properties do not follow a Normal distribution, where the value of p of the Shapiro-Wilk Test is less than 0.05 except for the CEC property (p>0.05).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…P. concerning soil pH, the studied soil fell into the normal category, while it falls into the high category of salinity expressed as dSm -1 .based on FAO (1979) the studied soil is considered non-calcareous soil due where the CaCO 3 percentage is less than 15%. These findings agree with many studies carried out in the same study area (AbdElghany et al, 2019, Ali et al, 2014, Ibrahim et al, 2015, Mohaseb et al, 2019, Nasef et al, 2009, and Shaban et al, 2010. Table 1 shows that all soil properties do not follow a Normal distribution, where the value of p of the Shapiro-Wilk Test is less than 0.05 except for the CEC property (p>0.05).…”
Section: Resultssupporting
confidence: 90%
“…5: Site-specific management zones of the study area fertilizers with an interest inorganic fertilizer as well as soil leaching process to reduce the concentration of salts tothe acceptable limit for crops. These findings are in agreement (Nasef et al, 2009;Shaban et al, 2010;Ali et al, 2014;Ibrahim et al, 2015;AbdElghany et al, 2019;Mohaseb et al, 2019) who all proved that the study area responds significantly to nitrogenous, phosphorous, and potassium fertilization, as well as demonstrated that conducting soil leaching process leads to a decrease in soil salinity and this is reflected in the increased crops yield. Therefore, following this approach in delineating the MZs will benefit those working in the agriculture field in determining the required quantities of mineral and organic fertilizers, as well as calculating the leaching water requirements for each MZ without extravagance where each MZ has requirements and quantities different from the other.…”
Section: Site-specific Management Zones Delineationsupporting
confidence: 88%
“…The highest N, P and protein contents were obtained from mixed inoculation combined with 75% of NPK level, which increased N contents of plant by 134 and 156%, P content by 60.1 and 94.6% and protein content by 135.2 and 156.1% compared with the control treatment in the two seasons, respectively. The previous studies have been reported similar findings on cowpea (Marwa et al, 2018), rice (Mohaseb et al, 2019), wheat (Attia and El Salam, 2016). El-Mekser et al (2016) recorded a significant increase in nitrogen, phosphorus and potassium level in biofertilized treatments corn plants relative to control, they also observed a significant increase in water-and salt-soluble proteins (albumins and globulins) fractions percentage by biofertilization application.…”
Section: Effect Of Mineral Fertilizer Levels and Biofertilizers On Chemical Contents Of Barley Plant During 2016 And 2017 Seasons Under Ssupporting
confidence: 76%